The Analysis of Students Online Shopping Behavior of Shopee Application in the Covid-19 Pandemic Era - Andrew Patrick Pasla; Marjam Mangantar; Regina Trifena Saerang (Universitas Sam Ratulangi, 2022)
The main issues of online shopping are not regarding its advantages and convenience that the platform gave to the people; but more about how the people try to approach the usage of online shopping which resulted in the existence of online shopping behavior. The current condition of online shopping behavior can be problematic if there are no further explanation regarding the phenomenon. The purpose of this study is to find out the student online shopping behavior of Shopee Application during the pandemic era, particularly the users arestudents of IBA Unsrat. This study uses a qualitative method and interview toward informants were conducted in order to gain information regarding the phenomenon. The findings of this study shows that the condition of online shopping behavior within Shopee application are in line with the current situation. The changes that made by the company made the costumers feel easier and safer to use the application during this limited condition. Based on the result, the researcher provided several recommendations such as check and balance system regarding the current products that can be done by the company and a more comprehensive understanding about the usage of online shopping media for the costumers